A Review of Big Data in Smart Farming (International Journal of Innovative Research in Computer Science & Technology, 2022)
Intelligent agro is now a growing concept  that accentuates employment of ICT inside cyber-physical  farmland managerial chain. The said growth is projected to  be accelerated by newer advancements such as the Internet  of Thing (IoT) & Mobile computing, which will enable  ranchers to deploy increased machines with machine  intelligence. All of that is represented by the Data Analysis  phenomenon that alludes to massive volumes of data of  different forms that may be gathered, processed, and used  to make decisions. One purpose of current research is to  get a better knowledge of the present state of Big Data  processing in Precision Agriculture and even to uncover  underlying accompanying psychosocial challenges that  need to be addressed. A systematic technique has been  used to construct a philosophical paradigm for assessment,  which is often used in subsequent study on the issue. With  regards to basic productivity, our research found that Data  Analysis implementations in Agriculture 5.0 have an  influence on this kind of agriculture distribution network.  In farming activities, information systems is increasingly  getting used to provide actionable analytics, dictate  genuine logistical decisions, and reimagine workflows in  way to build game-changing marketing strategies. As a  consequence, many authors anticipate that Big Data will  cause substantial alterations in the responsibilities &  economic dynamics between different parties in current  food distribution system ecosystems. The partner  panorama exhibits a fascinating interaction involving giant  virtual enterprises, venturing capitalists, &, on occasion,  little entrepreneurs as well as entrants. Most municipal  institutions, make accessible data available on the  provision provided customers' confidentiality be  respected. From a sociological aspect, the authors suggest  concentrating research on management policies including  such accountability and acceptable business strategies for  information exchange in diverse distribution network  settings.
Keywords: Agriculture; Big Data; Machines; Smart Farming